Foreign direct investment in Kujawsko-Pomorskie Voivodship - Piotrowicz, Artur; Sobczak, Iwona (Torun International Studies, 2010)
The inflow of foreign direct investment to kujawsko-pomorskie voivodship make chance to complete shortage of own investment possibilities in economy of region. In that paper is described the structure of foreign direct investment in kujawsko-pomorskie voivodship in 1999–2006 and the companies with foreign capital in this voivodship. There are presented also problems connected with foreign direct investment and labor market in kujawsko- pomorskie voivodship.